Dapatkah R&D Memperkuat Pengaruh Human Capital dan Environmental Performance Terhadap Nilai Pasar Perusahaan? - Eugenius Besli (Universitas Sarjanawiyata Tamansiswa, 2023)
The research aims to test whether research & development are able to strengthen the relationship human capital and environmental performance on firm market value. Several studies related to human capital and environmental performance on firm market values ​​show different results. The difference in results make it possible to moderate research and development costs. The research was conducted manufacturing companies listed on the IDX for 2020-2022 using purposive sampling. The research design uses a quantitative descriptive method with SPSS multiple linear regression analysis. The results showed that human capital has a positive effect on firm market value and environmental performance has no effect on firm market value, while research and development costs cannot be a moderating variable.